1989
DOI: 10.1093/eurheartj/10.suppl_f.44
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic assessment of human coronary artery endothelial function by measurement of endothelium-dependent vasodilation

Abstract: In isolated atherosclerotic human coronary arteries endothelium-dependent vascular relaxation is abolished with acetylcholine whereas another EDRF-dependent vasodilator, substance P, still produces significant relaxation. To study further these in vitro findings, graded doses of acetylcholine and substance P, which produced no systemic effects, were infused into the left anterior descending artery of patients with angiographically moderate coronary artery disease. The effects of acetylcholine and substance P o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…These effects include its role in stimulating immune function,14 tissue repair,15 increased vascular permeability,16"17 response to hypoxia3 and its role as a mediator of inflammation,18 potent peripheral and coronary vasodilator, and modulator of coronary blood flow.19-22 The two latter effects are associated with SP-mediated endothelial prostacyclin (PGI2) production23'24 and endothelium-dependent production of endothelium-derived relaxing factor (EDRF). 25,26 Evidence from recent studies27-29 suggests that sensory neuropeptides may also play an important role in regulating in vitro cellular proliferation. However, the role of SP on arterial endothelial cell growth is unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These effects include its role in stimulating immune function,14 tissue repair,15 increased vascular permeability,16"17 response to hypoxia3 and its role as a mediator of inflammation,18 potent peripheral and coronary vasodilator, and modulator of coronary blood flow.19-22 The two latter effects are associated with SP-mediated endothelial prostacyclin (PGI2) production23'24 and endothelium-dependent production of endothelium-derived relaxing factor (EDRF). 25,26 Evidence from recent studies27-29 suggests that sensory neuropeptides may also play an important role in regulating in vitro cellular proliferation. However, the role of SP on arterial endothelial cell growth is unknown.…”
mentioning
confidence: 99%
“…[19][20][21][22] The two latter effects are associated with SP-mediated endothelial prostacyclin (PGI2) production23'24 and endothelium-dependent production of endothelium-derived relaxing factor (EDRF). 25,26 Evidence from recent studies27-29 suggests that sensory neuropeptides may also play an important role in regulating in vitro cellular proliferation. However, the role of SP on arterial endothelial cell growth is unknown.…”
mentioning
confidence: 99%
“…Vasoactive drugs should be withdrawn in due time prior to all quantitative coronary angiographic studies. Other factors influencing CVT, such as catecholamines, metabolites, changes of blood pH, changes of coronary flow or endogenous substances modifying the release of EDRF in the coronary arterial endothelium should be considered and be kept as constant as possible [15,16,18,[31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that endotheliumdependent vasodilation is impaired in several pathological conditions including atherosclerosis and hypertension. [23][24][25] The endothelium has a significantly heterogeneous structure and function among organs, and there are differences between macrovascular and microvascular endothelium. 26 A number of studies have shown that cardiac microvascular EC play important roles in physiological and pathological conditions such as hypertrophy, ischemia and collateral development.…”
Section: Microvascular and Macrovascular Endothelial Functionmentioning
confidence: 99%